Congenital disorders of glycosylation: Still "hot" in 2020 - Ondruskova, Nina; Cechova, Anna; Hansikova, Hana; Honzik, Tomas; Jaeken, Jaak (Biochimica et biophysica acta. General subjects, 2021)
BACKGROUND: Congenital disorders of glycosylation (CDG) are inherited metabolic diseases caused by defects in the genes important for the process of protein and lipid glycosylation. With the ever growing number of the known subtypes and discoveries regarding the disease mechanisms and therapy development, it remains a very active field of study. SCOPE OF REVIEW: This review brings an update on the CDG-related research since 2017, describing the novel gene defects, pathobiomechanisms, biomarkers and the patients' phenotypes. We also summarize the clinical guidelines for the most prevalent disorders and the current therapeutical options for the treatable CDG. MAJOR CONCLUSIONS: In the majority of the 23 new CDG, neurological involvement is associated with other organ disease. Increasingly, different aspects of cellular metabolism (e.g., autophagy) are found to be perturbed in multiple CDG. GENERAL SIGNIFICANCE: This work highlights the recent trends in the CDG field and comprehensively overviews the up-to-date clinical recommendations.
Keywords: lipidy; Pathobiomechanism; proteiny; Therapy; vrozené poruchy glykosylace; mutace; Metabolic Networks and Pathways; CDG; glykosylace; Lipids; Novel phenotypes; Glycosylation; Lipid Metabolism; Mutation; zvířata; Humans; Clinical guidelines; metabolismus lipidů; Congenital Disorders of Glycosylation; metabolické sítě a dráhy; Proteins; lidé; Animals